2016
DOI: 10.1016/j.saa.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel perylene diimides containing aromatic amino acid side chains

Abstract: Perylene diimide derivatives have attracted initial interest as industrial dyes. Recently, much attention has been focused on their strong π–π stacks resulting from the large PDI aromatic core. These PDI stacks have distinct optical properties, and provide informative models that could mimic light-harvesting systems and initial charge transfer typical of photosynthetic systems. The absorption property of PDI derivatives may be tuned from visible to near-infrared region by peripheral substitution. We have studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Although morphology control has been studied for a variety of PDI systems, many of the approaches used to control aggregation have been performed in halogenated or organic solvents. There has been an increasing interest in creating PDIs that are soluble in aqueous or more polar solvents . Many of these molecules use hydroxy‐terminated, large dendritic or oligosilsesquioxane groups to deter aggregation and dimerization of the PDIs in these solutions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although morphology control has been studied for a variety of PDI systems, many of the approaches used to control aggregation have been performed in halogenated or organic solvents. There has been an increasing interest in creating PDIs that are soluble in aqueous or more polar solvents . Many of these molecules use hydroxy‐terminated, large dendritic or oligosilsesquioxane groups to deter aggregation and dimerization of the PDIs in these solutions.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] The aggregate morphology andc rystal structure can also be controlled. [14][15][16][17][18][19][20][21][22] PDIs can interactt oc reate chiral or helical structures, [23] wires, [20,24] "fish-tail" structures, [25] liquid crystal phases, [26] self-assembled mixed aggregates, [27][28][29] and crystallites of varying degrees of disorder. [30,31] These molecular morphologyand electronic modificationshave facilitated many potential materials applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different aminoacids that have been employed for synthesizing water-soluble PDIs are particularly glycine, alanine, phenylalanine, leucine, methionine, tyrosine, lysine, and aspartic acid. [11][12][13] Roy et al synthesized PDI-tyrosinebased hydrogelator which was found to exhibit excellent photo-switching behavior with a high photoresponse value within the pH range 5.00 to 9.00. [14] Schmidt et al synthesized alanine/lysine-based chiral, water-soluble PDI derivatives and studied the circular dichroic effects in buffer solution and its aggregation behavior having interesting aggregation properties.…”
Section: Introductionmentioning
confidence: 99%
“…They have been versatilely employed as fluorescent labels, membrane markers, or anti‐inflammatory agents . The striking photostability of PBI expressed in long fluorescence lifetimes of ≈4–5 ns and monoexponential fluorescence decays over at least 16 ns becomes obvious in comparison to other conventional fluorescent probes such as cy5 (0.91 ns), alexa fluor 647 (1.04 ns), and rhodamine B (1.74 ns) with significantly lower lifetimes. The superior long‐term photostability of PBIs compared to common fluorophores like coumarin or fluorescein was recently demonstrated in a study by Zimmerman and co‐workers; additionally, they were able to improve the FQYs of PBIs by site‐isolation of the fluorophore in the imide positions.…”
Section: Introductionmentioning
confidence: 99%